FINANCING VENTURE CAPITAL INVESTMENTS IN A COVID-19 LANDSCAPE - WILK, MARCIN (Management and Administration Journal, 2021)
This article attempts to identify factors negatively affecting economic growth in developing regions and to answer the question of what aid is effective in the form of individualized investment activities that correspond to selected development problems in startups and small enterprises. The use and implementation of capital instruments based on commercial investment standards allows to increase the efficiency of managing financial intervention processes in times of crisis, as well as strengthening local enterprises by improving their capital position. In addition, it enables the implementation of valuable products and services based on new technologies.